2015
DOI: 10.1021/jacs.5b01252
|View full text |Cite
|
Sign up to set email alerts
|

Brute-Force Hyperpolarization for NMR and MRI

Abstract: Hyperpolarization (HP) of nuclear spins is critical for ultrasensitive nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI). We demonstrate an approach for >1500-fold enhancement of key small-molecule metabolites: 1-(13)C-pyruvic acid, 1-(13)C-sodium lactate, and 1-(13)C-acetic acid. The (13)C solution NMR signal of pyruvic acid was enhanced 1600-fold at B = 1 T and 40 °C by pre-polarizing at 14 T and ∼2.3 K. This "brute-force" approach uses only field and temperature to generate HP. The noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 47 publications
1
121
0
2
Order By: Relevance
“…For measurement, the sample was transferred to a field of 1 T and rapidly dissolved and measured at 40°C [22]. Although higher polarization can be obtained at higher fields and lower temperatures, there are also limitations to these approaches.…”
Section: Other Hyperpolarization Methodsmentioning
confidence: 99%
“…For measurement, the sample was transferred to a field of 1 T and rapidly dissolved and measured at 40°C [22]. Although higher polarization can be obtained at higher fields and lower temperatures, there are also limitations to these approaches.…”
Section: Other Hyperpolarization Methodsmentioning
confidence: 99%
“…The development of SEOP is rooted in the pioneering work of Kastler, [31] who was recognized with the Nobel Prize in physics for demonstrating that electronic spin order can be created in alkali metal vapors using circularly polarized laser light. Later Bouchiat, Carver, and Varnum [32] showed that the addition of 3 He to the gas mixture permitted helium nuclear spins to be polarized by spin-exchange collisions with the optically pumped alkali vapor atoms-work that was extended to 129 Xe by Grover. [33] The rich physics of SEOP has been extensively explored by Happer, Cates, Chupp, Walker, and many others (e.g.…”
Section: Seopmentioning
confidence: 99%
“…Although the vast majority of SEOP experiments have employed the spin I=1/2 noble gas isotopes 129 Xe and 3 He, the quadrupolar species 21 Ne (I=3/2), [36] 83 Kr (I=9/2), [37] and 131 Xe [38] (I=3/2) can also be polarized via this method. For the alkali metal vapor, Rb is most-commonly employed for practical reasons-including its low melting point [39] (facilitating vaporization) and the availability of high-powered lasers resonant with its D1 transition [40] ; however, K and Cs are also utilized (particularly for 3 He [41] and 129 Xe, [42] respectively).…”
Section: Seopmentioning
confidence: 99%
See 2 more Smart Citations